2021
DOI: 10.53730/ijhs.v5n3.1503
|View full text |Cite
|
Sign up to set email alerts
|

Psychological features of post-COVID syndrome course

Abstract: Recently, the so-called post-COVID syndrome has been making itself felt more and more. Given the fact that diseases associated with coronavirus have acquired the character of an epidemic since the end of 2019, the features of the impact of this virus on the bodies of modern people have not yet been studied at all. The study analyses the features of post-COVID syndrome. The authors investigated the features of the course of "long COVID" in people with various psychological characteristics – anxiety, temperament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The overwhelming majority of experts, post-COVID syndrome is a mental disorder that is a kind of reaction to the COVID-19 pandemic, according to (Bocheliuk et al, 2021). This disorder has already affected 15% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming majority of experts, post-COVID syndrome is a mental disorder that is a kind of reaction to the COVID-19 pandemic, according to (Bocheliuk et al, 2021). This disorder has already affected 15% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher found that traumatic stress is a normal reaction of the body to a threat; however, a severe course triggers self-preservation mechanism storing negative properties in the memory that the person will automatically avoid in the future. Traumatic stress is a general reaction to a stimulus that destroys energy shield, physiological, adaptive, and psychological capabilities of a person (Bocheliuk et al, 2021). The traumatic stress does not always preserve the events experienced in the memory, sometimes acting as an accompanying way of protection.…”
Section: Discussionmentioning
confidence: 99%
“…In the dynamic course of PTSD, progressive cerebral-organic disorders come to the fore, which in the future gradually turn into a chronic generalized decrease in the core of the personality and sometimes its destruction. Diseases resulting from physical trauma are characterized by a chronic, progressive, and, therewith, disabling process (Bocheliuk et al, 2021;Kang et al, 2023). However, most significantly, the combination of neurotic (organic) and psychopathological syndromes is distinctive in the context of PTSD, as overt neurotic (or behavioral) disorders can hide clinically less obvious neurotic (organic) symptoms, while serious neurological disorders can mask serious PTSD.…”
Section: Discussionmentioning
confidence: 99%